Assessment of Image Quality and Lesion Detectability With Digital PET/CT System - Delcroix, Olivier; Bourhis, David; Keromnes, Nathalie; Robin, Philippe; Le Roux, Pierre-Yves; Abgral, Ronan; Salaun, Pierre-Yves; Querellou, Solène (Frontiers in Medicine, 2021)
Purpose: The aim of this study was to assess image quality and lesion detectability acquired with a digital Positron Emission Tomography/Computed Tomography (PET/CT) Siemens Biograph Vision 600 system. Material and Methods: Consecutive patients who underwent a FDG PET/CT during the first week of use of a digital PET/CT (Siemens Biograph Vision 600) at the nuclear medicine department of the university hospital of Brest were analyzed. PET were realized using list mode acquisition. For all patients, 4 datasets were reconstructed. We determined, according to phantom measurements, an equivalent time acquisition/reconstruction parameters pair of the digital PET/CT corresponding to an analog PET/CT image quality (“analog-like”) as reference dataset. We compared the reference dataset with 3 others digital PET/CT reconstruction parameters, allowing a decrease of emission duration: 60, 90, and 120 s per bed position. Three nuclear medicine physicians evaluated independently, for each dataset, overall image quality [Maximal Intensity Projection (MIP), noise, sharpness] using a 4-point scale. Physicians assessed also lesion detection capability by reporting new visible lesions on each digital datasets with their confidence level in comparison with analog-like dataset. Results: Ninety-eight patients were analyzed. Image quality of MIP (IQMIP), sharpness (IQSHARPNESS), and noise (IQNOISE) of all digital datasets (60, 90, and 120 s) were better than those evaluated with analog-like reconstruction. Moreover, digital PET/CT system improved IQMIP, IQNOISE, and IQSHARPNESS whatever the BMI. Lesion detection capability and confidence level were higher for 60, 90, 120 s per bed position, respectively, than for analog-like images. Conclusion: Our study demonstrated an improvement of image quality and lesion detectability with a digital PET/CT system.